1980
DOI: 10.1042/bj1880091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nucleotides, cations and nucleoside triphosphatase inhibitors on the release of ribonucleic acid from isolated rat liver nuclei

Abstract: The reasons underlying reported discrepancies in the effects of ATP, ADP, adenosine 5'-[Ify-methyleneltriphosphate, AMP + PP1, p-chloromercuribenzoate and F-on RNA efflux from isolated rat liver nuclei and on nuclear-envelope nucleoside triphosphatase activity were investigated. The stimulatory effect of ADP was attributed to myokinase activity associated with the nuclei; this activity was eluted on repeated washing with nuclear incubation medium. In the absence of Ca2+ and Mn2+, ATP, adenosine 5'-[Iymethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 35 publications
4
8
0
Order By: Relevance
“…This model is in agreement with the observation that ATPases are regulated by phosphorylation-dephosphorylation processes (55). Moreover, this model is also in agreement with the findings of Agutter, who has proposed that the dephosphorylation of the nuclear envelope may increase NTPase activity, and that poly(A)-containing RNA (a known activator of NTPase and mRNA effilux) may increase enzyme activity through a dephosphorylation reaction (43). Further, this model is in agreement with the cytochemical studies of Vorbrodt and Maul, who have observed that the NTPase of the nuclear envelope is associated with the nuclear pore complex and mRNA particles translocating through the nuclear pores (51).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This model is in agreement with the observation that ATPases are regulated by phosphorylation-dephosphorylation processes (55). Moreover, this model is also in agreement with the findings of Agutter, who has proposed that the dephosphorylation of the nuclear envelope may increase NTPase activity, and that poly(A)-containing RNA (a known activator of NTPase and mRNA effilux) may increase enzyme activity through a dephosphorylation reaction (43). Further, this model is in agreement with the cytochemical studies of Vorbrodt and Maul, who have observed that the NTPase of the nuclear envelope is associated with the nuclear pore complex and mRNA particles translocating through the nuclear pores (51).…”
Section: Discussionsupporting
confidence: 80%
“…RNA transport in vitro involves both intranuclear RNA processing and subsequent efflux, and a source of high-energy phosphate such as ATP is necessary for transport but not processing (32,52,53 (33), and cyclic AMP stimulates both functions whereas NaF inhibits them (32,33,(52)(53)(54). Treatment with trypsin and sulfhydryl blockers inactivates both functions (32,43). Moreover, histochemical studies have suggested that the NTPase resides in the nuclear pore complex (32) and is associated with ribonucleoproteins that are being translocated through the nuclear pore complex (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also indicates that up to 15% of the envelopes are leaky, in accordance with previous experiments (1). Envelope NTPase activity is stimulated by ribonucleic acids, especially by poly(A) (23). As shown in Table 2, this effect is distinct in the leaky DNase envelopes.…”
supporting
confidence: 76%
“…2 shows the kinetics of the release of [3H]RNA from these preparations of nuclei, incubated in the medium described in Materials and Methods, as well as the effects of omitting ATP and its regenerating system, and of substituting the non-hydrolysable P,y-imino analogue of ATP, adenosine 5'-[P,y-imino]triphosphate (AdoPP[NH]P). In other respects the conditions were the same as those used by previous investigators [12,37] with minor variations (the use of creatine kinase and creatine phosphate instead of phosphoenolpyruvate and pyruvate kinase as ATP-regenerating system, and of Escherichia coli RNA instead of yeast RNA as carrier).…”
Section: Maintenance Qf Nuclear Integrity With R N a Release In Vitromentioning
confidence: 99%